Pengaruh Experiential Learning dan Kreativitas Siswa SDN Pelamunan Kabupaten Serang Terhadap Hasil Belajar Matematika - Yani Supriani (Universitas Serang Raya, 2018)
The main purpose of this research is to know the influence and interaction between experiential learning model and student creativity toward the result of mathematic learning.Population of this research is student of VIA and VIB class SDN Pelamunan Serang, 2017/2018 year. Sample of this research is taken by using Multi Stage Random Sampling. Research design used in this research is factorial design 2X2 with three variables which contains two independent variables are experiential learning model and student creativity; and one dependent variable is the result of mathematic learning.Collecting of the data is conducted by using test technique (the result of mathematic learning), questioner technique (student creativity) and document technique (experiential learning model). Data collected is analyzed by using ANAVA two sides and it is continued with the tukey test because there is influence between experiential learning models with student creativity toward the result of mathematic learning. Before the data is being analyzed, it is conducted descriptive statistical analysis and data testing (normality and homogeneity tests). Result of the research shows that: (1) experiential learning model gives influence to the result of mathematic learning, it is showed by the result of anava where F count is (11,589) more and F-table for the significance level 5% (4,00); (2) student creativity gives influence to the result of mathematic learning, it is showed by the result of anava where the F-count (33,362) more than F-table for the significance level 5% (4,00); (3) there is interaction between experiential learning model and student creativity toward the result of mathematic learning, it is showed by F count (4,627) more than F table for the significance level 5% (4,00); (4) there is influence of the result of mathematic learning with experiential learning concept for the student’s creativity, it is showed by the result of tukey test where the count test (17, 91) higher than t test.